Production of new growing media for algae in biodiesel production / Mohibah Musa … [et al.] - Musa, Mohibah; Ku Hamid, Ku Halim; Muhd Rodhi, Miradatul Najwa; Rosli, Nurul Liyana (Research Innovation Business Unit, 2014)
Photosynthetic algae comprise the trophic base of many ecosystems and have significant potential in contributing to sustainable bio-fuel production, carbon dioxide (co2) mitigation, and waste remediation. Rapid industrialization, increase in population and changes in consumption pattern directly and indirectly result in the generation of a large amount of municipal and industrial wastes, ranging from biodegradable to synthetic. In Malaysia, solid waste management has become a major environmental problem. Over 23,000 tonnes of waste is produced daily in Malaysia. By 2020, the amount is expected to have risen to 30,000 tonnes. The amount of waste generated continues to increase due to the rising population and development of the country. Less than 5% of the waste is being recycled. Sanitary land filling has been the most popular methods of solid waste disposal in many countries, including Malaysia. There are more than 296 landfills throughout Malaysia. Most of the landfills are open dumping grounds, and they pose serious environmental and social threats. Landfills have been accepted as the most economical and environment friendly way for the disposal of solid waste compared with other disposal methods, such as composting, incineration, and gasification. However, a major concerns associated with this disposal method is the leachate produced from the landfills. Landfills produce liquid leachates, which must be managed and remediate to prevent long-term community health impacts. Leachate is the water that contains dissolved and suspended solids resulting from the percolation of water that drains through the waste in the landfill. The constituents of the leachate include organic matters and inorganic matters which depend on the age of landfill and type of the waste. In the remediation of landfill leachate, fossil energy is expended to ensure continuing environmental quality. These considerable anthropogenic deposits and the leachates which ensue, embody unutilized elemental resources. Photosynthetic algae provide a remediation alternative, which simultaneously produces bio-resources with societal value from the biological assimilation of elemental nutrients within landfill leachate. In this study, a closed municipal solid waste landfill was bio-prospected for native algae with potential in remediating landfill leachate and bio-resource production. A previous study determined that the growth of the algae chlorella protothecoides, well-known in literature for its high lipid content, in various concentrations of leachate is possible on a lab-scale. This is likely due to the high concentrations of nutrients such as nitrogen and phosphorous in the leachate that provides for a nutritive growth media. However, further analysis is necessary on a lab-scale to determine optimal conditions for growth and lipid content, which will affect the quantity of biodiesel produced. Elemental analysis shows that leachate contains all required elements for photosynthetic growth; however, in cultivation experiments leachate exhibited a strong inhibitory effect on algae growth correlated with concentration. Through investigative experimentation, toxicity within landfill leachate was attributed to the presence of unionized ammonia. Growth of algae on leachate without ph control is inhibited above a 10 percent landfill leachate concentration. Algae growth is supported only under the appropriate conditions of ph regulation, which can be accomplished by the addition of carbon dioxide or hydrochloric acid to the algae culture. If ph regulation is applied, growth is possible in municipal solid waste (msw) landfill leachate concentrations of 100 percent, a value not reported in the current literature. Once the preliminary results are confirmed, scale-up to an industrial level will be developed using this data with environmental analysis. The expectation is to develop an industrial process for algal biodiesel production at the site that may be translated to facilities under similar circumstances.